2019
DOI: 10.1177/1744806919849201
|View full text |Cite
|
Sign up to set email alerts
|

X-ray induces mechanical and heat allodynia in mouse via TRPA1 and TRPV1 activation

Abstract: Radiotherapy-related pain is a common adverse reaction with a high incidence among cancer patients undergoing radiotherapy and remarkably reduces the quality of life. However, the mechanisms of ionizing radiation-induced pain are largely unknown. In this study, mice were treated with 20 Gy X-ray to establish ionizing radiation-induced pain model. X-ray evoked a prolonged mechanical, heat, and cold allodynia in mice. Transient receptor potential vanilloid 1 and transient receptor potential ankyrin 1 were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Intraperitoneal injection of capsazepine attenuated heat hyperalgesia but did not affect mechanical and cold allodynia in a murine model of cancer pain [ 23 ]. In intrathecal administration experiments, capsazepine transiently reversed mechanical and heat allodynia increased by X-ray [ 24 ] and relieved remifentanil-induced postoperative hyperalgesia [ 25 ]. In another study, intrathecal administration of capsazepine decreased the analgesic effect against thermal hyperalgesia induced by anandamide, endogenous cannabinoid receptor ligand, in the carrageenan model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of capsazepine attenuated heat hyperalgesia but did not affect mechanical and cold allodynia in a murine model of cancer pain [ 23 ]. In intrathecal administration experiments, capsazepine transiently reversed mechanical and heat allodynia increased by X-ray [ 24 ] and relieved remifentanil-induced postoperative hyperalgesia [ 25 ]. In another study, intrathecal administration of capsazepine decreased the analgesic effect against thermal hyperalgesia induced by anandamide, endogenous cannabinoid receptor ligand, in the carrageenan model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of TRPA1 and TRPV1 seems to mediate X-ray-induced mechanical and heat allodynia in mice (177).…”
Section: Activation By Lightmentioning
confidence: 97%
“…This is possibly due to sex-dependent expression of more specific heat and cold receptors involved in nociception, such as the transient receptor potential vanilloid (TRPV) family. [47][48][49][50][51] Previous studies have shown that high levels of 17ß-estradiol can induce mechanical and thermal hypersensitivities through TRPV1 sensitization in rodents. [52][53][54] Alternatively, testosterone has a protective effect against TRPV1 sensitization and reduces receptor expression.…”
Section: Discussionmentioning
confidence: 99%